PERANAN KEPALA SEKOLAH DALAM MENGEMBANGKAN ADMINISTRASI PERSONEL - Baharuddin, Baharuddin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2010)
The success of a head master in running administra-tive activities depends strongly on his leadership style. His leadership condition can be more complex due to the personnel number and school diversity. The social change, the increase of different roles in terms of school management functions and the rise of school demand also contribute to the complexity of the role of a head master. Basical-ly, the main role of a head master is to retain condusive envoronment of school for learning process. He is responsible for comportable classroom apart from his managerial responsibility including, plan-ning, organizing, leading and controlling.